Dermatologic manifestations of infective endocarditis - Rafael Tomaz Gomes; Larissa Rezende Tiberto; Viviane Nardin Monte Bello; Margarete Aparecida Jacometo Lima; Gisele Alborghetti Nai; Marilda Aparecida Milanez Morgado de Abreu (Sociedade Brasileira de Dermatologia, 2016)
Abstract Despite advances in diagnosis and treatment, infective endocarditis still shows considerable morbidity and mortality rates. The dermatological examination in patients with suspected infective endocarditis may prove very useful, as it might reveal suggestive abnormalities of this disease, such as Osler's nodes and Janeway lesions. Osler's nodes are painful, purple nodular lesions, usually found on the tips of fingers and toes. Janeway lesions, in turn, are painless erythematous macules that usually affect palms and soles. We report a case of infective endocarditis and highlight the importance of skin examination as a very important element in the presumptive diagnosis of infective endocarditis.